Pattern of ileal perforation in our experience; a tertiary care centre in Eastern India - Jha, Pawan Kumar; Chandran, Rajnish; Jaiswal, Pradeep; Kumar, Anurag; Seema, Kumari; Singh, Digbijay Kumar; Kumar, Ashwini; Kumar, Mukesh (International Surgery Journal, 2018)
Background: Perforation peritonitis is one of the common acute abdomen admitted in emergency department for emergency laparotomy. Pattern and aetiology of ileal perforation varies from developed and developing countries where infectious diseases are still highly prevalent. Methods: This was a prospective study conducted over 3 years period in Indira Gandhi Institute of Medical Sciences, Patna. Total 118 patients were enrolled for this study after confirmation of ileal perforation on exploratory laparotomy. Results: Out of total 118 patients 52 cases (44%) were in traumatic, typhoid causes perforation in 86% (57 cases) tuberculosis in 14% (9 cases) and 66 cases (56%) were in non-traumatic group, penetrating injury is more common than blunt trauma abdomen. Males are more commonly affected than females in among all cases of ileal perforation. Patients with traumatic ileal perforation seek early medical attention as most of the patients (44%) admitted within 12 hours after accident where as in case of non-traumatic cases 53% patients admitted after 2 days. Most common operative procedure performed is Loop ileostomy in case of non-traumatic perforation (49%) and Resection and anastomosis preferred in traumatic perforation (63%). Mortality rate is about 20% in all types of perforation. Conclusions: In developing countries like India typhoid perforation is still most common cause of ileal perforation. Loop ileostomy is more preferred procedure in infectious cases but resection and anastomosis in case of traumatic perforation in our institute.